A survey of intrusion detection system using case study Kuwait governments entiteis - Alenezi, Khalid; Taha Alshaikhli , Imad Fakhri; al-kandari, Abdul Rahman; Al-Tayyar, Lulwa Ziad (2014)
The tremendous developments in information technology in our world requires a modern way of Intrusion Detection Systems to prevent damage or compromise the system. Computer Emergency Response Team handles the computer incidents in the computer systems. In the Kuwaiti government entities may find some weaknesses in Intrusion Detection Systems this research dwells for these points by distribute a questionnaire in government’s employees. Then try to find the ideal solutions for these problems to reach the maximum level of security in Kuwait government entities. In this paper found that the information security and especially the intrusion detection system in Kuwait government needs to be more efficient by ensure that the organizations use the principles and criteria of using IDS and Cyber security. In the end of this paper there are some recommendations for the organization to improve their system security.